Effectiveness of Birth Massage and Heat Theraphy in Reducing Labor Pain - Evi Rinata; Rafhani Rosyidah (JURNAL KEBIDANAN, 2020)
Labor pain is a physiological process with a different intensity for each individual. Lamaze in Bobak (2010) states that 85 - 90% of deliveries take place with pain, and only 10-15% of deliveries take place without pain. Monitoring pain in labor is very important because this is a measure of whether labor can proceed normally or end with an action due to complications. Various attempts were made to overcome labor pain both pharmacologically and non-pharmacologically. One method of handling pain in a non-pharmacological way is to provide birth massage and heat therapy. The purpose of this study was to determine the effectiveness of the combination of birth mass and heat therapy to reduce labor pain in the first phase of active phase. The design in this study is Quasi Experimental Design with Nonequivalent Control Group Design method using pretest - posttest design. The population used was the first phase active mothers in RB Nuril Masrukhah Sidoarjo that met the inclusion criteria. The sampling technique used was consecutive sampling. Data collection was carried out by observing 4 groups of maternal using pre-test and post-test with an observation sheet containing a scale of pain scale assessment with behavioral observation (FLACC behavioral scale). Data analysis using One Way Anova with significance level α = 0.05. The conclusion of this study is that there is no difference in labor pain between groups given a combination of birth massage and heat therapy with a group given birth massage, there is no difference in labor pain between groups given a combination of birth massage and heat therapy with a group given heat therapy, but there are differences between groups that are given a combination of birth massage and heat therapy with the group without treatment.